The entring book of Roger Morrice, 1677-1691, Volume IV the reign of James II, 1687-1689 - Morrice, Roger 1628-1702 (Boydell & Brewer, 2007)
The Entring Book is the longest and richest diary of public life in England during the era of the Glorious Revolution. Spanning the years 1677 to 1691, in nearly a million words, it records the downfall of the House of Stuart. This is a chronicle not only of politics and religion, but also of culture and society, gossip and rumour, manners and mores, in a teeming metropolis risen phoenix-like from the Great Fire. Its author, Roger Morrice, was a Puritan clergyman turned confidential reporter for leading Whig politicians - well-connected, a barometer of public opinion, and supremely well-informed. Written just twenty years after Pepys's Diary, the Entring Book depicts a darker England, thrown into a great crisis of 'popery and arbitrary power'